Association between the ACE‑I/D polymorphism and nicotine dependence amongst patients with lung cancer. Issue 6 (14th September 2020) - NADALIN, SERGEJ; FLEGO, VELJKO; PAVLIĆ, SANJA DEVIĆ; VOLARIĆ, DARIAN; BADOVINAC, ANĐELKA RADOJČIĆ; KAPOVIĆ, MILJENKO; RISTIĆ, SMILJANA
No abstract available